The PARENT model: a pathway approach for understanding parents' role after early childhood mild traumatic brain injury. Issue 5 (13th June 2021) - Beauchamp, M. H.; Séguin, M.; Gagner, C.; Lalonde, G.; Bernier, A.
Abstract: Objective: Mild traumatic brain injury (mTBI or "concussion") is a highly prevalent health condition in children, and those under the age of 6 years have the highest rate of Emergency Department presentation for suspected head injuries. The outcome of mTBI is determined by a range of child (injury, biological, functional) and environmental (socio-economic status, parent, family) factors. The aim of this work is to present evidence supporting the central role of parental and familial factors in pediatric mTBI recovery, and to illustrate ways in which parental factors can especially influence the outcome of early mTBI, defined as injuries sustained by infants, toddlers and preschoolers. Method: The manuscript first presents a topical review of empirical studies providing evidence that family functioning and parental factors such as their mental or affective state, parenting style, and the quality of their interactions with their child, are affected by and determine the course of recovery after pediatric mTBI. Then, a pathway approach and conceptual model are proposed to illustrate probable scenarios associated with how parents detect and react to their child's post-concussive symptoms and changes in behavior after early mTBI. Conclusion: The "Perception, Attribution, and Response after Early Non-inflicted Traumatic Brain Injury" (PARENT) model suggests that parental roles and factors are especially influential in the context of early brain injuries, and that parents' ability to perceive, attribute and respond to the symptoms experienced by their child in a well-adjusted and adaptive manner critically sets the direction and rhythm of the early mTBI recovery process.